Apoptosis of germ cells in the normal testis of the Japanese quail (Coturnix coturnix japonica). (December 2020) - Zakariah, Musa; Ibrahim, Mohammed I.A.; Molele, Reneilwe A.; McGaw, Lyndy J.
Highlights: Apoptosis of germ cells in the normal testis of Japanese quails was observed for the first time. High frequency of apoptosis of germ cells in pre-pubertal and aged birds were detected. Electron microscopy is one of the most sensitive techniques in confirming the TUNEL essay, An imbalance between degeneration and regeneration of germ cells can lead to infertility. Abstract: It has been established that excess germ cells in normal and in pathological conditions are removed from testicular tissue by the mechanism of apoptosis. Studies on germ cell apoptosis in avian species are grossly lacking, and there are only a few reports on induced germ cell degenerations in the testis tissue of birds. This study was designed to investigate the process of apoptosis of germ cells in the Japanese quail ( Coturnix coturnix japonica ). Germ cell degenerations were investigated in birds of all age groups, namely pre-pubertal, pubertal, adult, and aged. Apoptosis of germ cells in the quails, as shown by hematoxylin & eosin (H&E), TdT dUTP Nick End Labeling (TUNEL) assay and electron microscopy, was similar to that observed in previous studies of germ cells and somatic cells of mammalian species. The observed morphological features of these apoptotic cells ranged from irregular plasma and nuclear membranes in the early stage of apoptosis to rupture of the nuclear membrane, condensation of nuclear material, as well as fragments of apoptotic bodies, in later stages of apoptosis. In the TUNEL-positive cell counts, there was a significant difference between the mean cell counts for the four age groups (P < 0.05). Post hoc analysis revealed a highly significant difference in the aged group relative to the pubertal and adult age groups, while the cell counts of the pre-pubertal group were significantly higher than those of the pubertal group. However, there was no significant difference between cell counts of the pre-pubertal and the adult, and between the pre-pubertal and the aged groups.